α-mangostin improves glucose uptake and inhibits adipocytes differentiation in 3T3-L1 cells via PPARgamma, GLUT4, and leptin expressions - Taher, Muhammad; Mohamed Amiroudine, Mohamed Zaffar Ali; Tengku Zakaria, Tengku Muhamad Faris Syafiq; Deny Susanti,; Jauhari Arief Ichwan, Solachuddin; Kaderi, Mohd Arifin; Ahmed, Qamar Uddin; Zakaria, Zainul Amiruddin (Hindawi Publishing Corporation, 2015)
Obesity has been often associated with the occurrence of cardiovascular diseases, type 2 diabetes, and cancer. The development of obesity is also accompanied by significant differentiation of preadipocytes into adipocytes. In this study, we investigated the activity of α-mangostin, a major xanthone component isolated from the stem bark of G. malaccensis, on glucose uptake and adipocyte differentiation of 3T3-L1 cells focusing on PPARγ, GLUT4, and leptin expressions. α-Mangostin was found to inhibit cytoplasmic lipid accumulation and adipogenic differentiation. Cells treated with 50 μM of α-mangostin reduced intracellular fat accumulation dose-dependently up to 44.4% relative to MDI-treated cells. Analyses of 2-deoxy-D-[3H] glucose uptake activity showed that α-mangostin significantly improved the glucose uptake ( P < 0.05 ) with highest activity found at 25 μM. In addition, α-mangostin increased the amount of free fatty acids (FFA) released. The highest glycerol release level was observed at 50 μM of α-mangostin. qRT-PCR analysis showed reduced lipid accumulation via inhibition of PPARγ gene expression. Induction of glucose uptake and free fatty acid release by α-mangostin were accompanied by increasing mRNA expression of GLUT4 and leptin. These evidences propose that α-mangostin might be possible candidate for the effective management of obesity in future.